Can a single ammonia and water molecule enhance the formation of methanimine under tropospheric conditions?: kinetics of •CH2NH2 + O2 (+NH3/H2O) - Dash, Manas Ranjan; Ali, Mohamad Akbar (Frontiers in Chemistry, 2023)
The aminomethyl (•CH2NH2) radical is generated from the photo-oxidation of methylamine in the troposphere and is an important precursor for new particle formation. The effect of ammonia and water on the gas-phase formation of methanimine (CH2NH) from the •CH2NH2 + O2 reaction is not known. Therefore, in this study, the potential energy surfaces for •CH2NH2 + O2 (+NH3/H2O) were constructed using ab initio//DFT, i.e., coupled-cluster theory (CCSD(T))//hybrid-density functional theory, i.e., M06-2X with the 6-311++G (3df, 3pd) basis set. The Rice−Ramsperger−Kassel−Marcus (RRKM)/master equation (ME) simulation with Eckart’s asymmetric tunneling was used to calculate the rate coefficients and branching fractions relevant to the troposphere. The results show 40% formation of CH2NH at the low-pressure (<1 bar) and 100% formation of CH2NH2OO• at the high-pressure limit (HPL) condition. When an ammonia molecule is introduced into the reaction, there is a slight increase in the formation of CH2NH; however, when a water molecule is introduced into the reaction, the increase in the formation of CH2NH was from 40% to ∼80%. The calculated rate coefficient for •CH2NH2 + O2 (+NH3) [1.9 × 10−23 cm3 molecule−1 s−1] and for CH2NH2 + O2 (+H2O) [3.3 × 10-17 cm3 molecule-1 s-1] is at least twelve and six order magnitudes smaller than those for free •CH2NH2 + O2 (2 × 10−11 cm3 molecule−1 s−1 at 298 K) reactions, respectively. Our result is consistent with that of previous experimental and theoretical analysis and in good agreement with its isoelectronic analogous reaction. The work also provides a clear understanding of the formation of tropospheric carcinogenic compounds, i.e., hydrogen cyanide (HCN).